2008
DOI: 10.1007/s10562-008-9708-x
|View full text |Cite
|
Sign up to set email alerts
|

High Activity in Catalytic Oxidation of Benzyl Alcohol with Molecular Oxygen over Carboxylic-Functionalized Carbon Nanofiber-Supported Ruthenium Catalysts

Abstract: Carboxylic-functionalized carbon nanofibersupported Ru catalysts were prepared from the treatment of carbon nanofiber in HNO 3 -H 2 SO 4 media, followed by impregnation with RuCl 3 solution, dryness, calcination, and reduction procedures. Interestingly, carboxylic-functionalized carbon nanofiber-supported Ru catalysts show a good performance in oxidation of benzyl alcohol with molecular oxygen. In contrast, after partial removal of carboxylic groups on the surface of carbon nanofiber-supported Ru catalysts, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 50 publications
1
11
0
1
Order By: Relevance
“…The effect of functionalization on catalytic performance in the liquid phase oxidation of glycerol, appeared as a slight increase in the activity (TOF from 648 h À1 to 742 h À1 for CNTs and from 182 h À1 to 186 h À1 for CNF), but, surprisingly, the selectivity to C3 products was boosted from 33% for Au/CNTs to 70% for oxidized Au/CNTs and from 56% for Au/CNFs to 66% for oxidized Au/CNF. The importance of oxygen functionalities was highlighted by Tang et al 80 They showed that Ru supported on functionalized carbon nanofibers by treatment with HNO 3 65% and sulfuric acid 95-98% (393 K, 1 h) was very active in the benzyl alcohol oxidation and the partial removal of oxygen species by heat treatment led to a significant reduction of the catalytic conversion. The different Ru/CNF catalysts showed similar Ru particle size (3 nm), suggesting that the different amount of oxygen functionalities does not influence the particle size and distribution.…”
Section: Surface Propertiesmentioning
confidence: 99%
“…The effect of functionalization on catalytic performance in the liquid phase oxidation of glycerol, appeared as a slight increase in the activity (TOF from 648 h À1 to 742 h À1 for CNTs and from 182 h À1 to 186 h À1 for CNF), but, surprisingly, the selectivity to C3 products was boosted from 33% for Au/CNTs to 70% for oxidized Au/CNTs and from 56% for Au/CNFs to 66% for oxidized Au/CNF. The importance of oxygen functionalities was highlighted by Tang et al 80 They showed that Ru supported on functionalized carbon nanofibers by treatment with HNO 3 65% and sulfuric acid 95-98% (393 K, 1 h) was very active in the benzyl alcohol oxidation and the partial removal of oxygen species by heat treatment led to a significant reduction of the catalytic conversion. The different Ru/CNF catalysts showed similar Ru particle size (3 nm), suggesting that the different amount of oxygen functionalities does not influence the particle size and distribution.…”
Section: Surface Propertiesmentioning
confidence: 99%
“…Similarly, the SOCGs around Ru particles confined the polar unsaturated species in the vicinity of Ru particles. This confinement effect made the unsaturated species preferentially undergo hydrogenation over Ru particles rather than by-reactions in the bulk liquid phase, so higher glycol selectivities were obtained over Ru/CNFs-240 o C. Although the above effect of SOCGs on sorbitol hydrogenolysis has not been reported in previous studies, researchers have found that the interactions between SOCGs and reactants imposed positive or negative effects on many catalytic reactions, such as cinnamaldehyde hydrogenation over Ru/CNFs and Pt/CNFs [18,20,21], oxidation of benzyl alcohol over Ru/CNFs [22] and hydrodechlorination of chlorobenzenes over Pd/AC, Pd/graphite and Pd/ CNFs [23].…”
Section: Sorbitol Hydrogenolysismentioning
confidence: 99%
“…This open structure facilitates the diffusion of reactants and products by reducing steric hindrance. As regards their tuneable chemical nature, it is relatively easy to modify the surface chemistry of NC by, for instance, attaching oxygen surface groups that may have an impact not only on the active phase morphology but also on the catalyst activity [20][21][22]. The material thus constitutes a very promising support for use in various catalytic processes.…”
Section: Introductionmentioning
confidence: 99%